PROFIL INFEKSI CANDIDA ALBICANS PADA URINE WANITA DENGAN DIABETES MELITUS DI PUSKESMAS MUJUR PRAYA TIMUR TAHUN 2023 - Annisaturrahmah Himawan (Nusadaya Journal of Multidiciplinary Studies, 2026)
Candida albicans infection is an opportunistic fungal infection commonly found in individuals with weakened immune systems, including patients with diabetes mellitus. Hyperglycemic conditions in diabetic patients may increase the risk of microbial growth, including fungal infections in the urinary tract. This study aimed to describe the profile of Candida albicans infection in urine of women with diabetes mellitus at Mujur Public Health Center, East Praya, in 2023. This research used a descriptive method with a retrospective approach based on laboratory data and medical records. The samples consisted of urine from female patients with diabetes mellitus who met the inclusion criteria. Laboratory examination was performed using microscopic analysis and culture on Sabouraud Dextrose Agar (SDA). The results showed the presence of Candida albicans in several urine samples with specific characteristics. This finding indicates that patients with diabetes mellitus have a higher risk of fungal infection in the urinary tract.